Hypertonic Cryohemolysis of Mammalian Erythrocytes in Media with Different Cation Compositions - Ershov, S. S.; Orlova, N. V.; Shpakova, N. M. (Problems of Cryobiology and Cryomedicine, 2007)
The effect of media, containing either Li+, Na+, K+ monovalent cations or combination (Na++K+) (2,400 mOsm/kg osmolarity) on a time dependence proceeding of hypertonic cryohemolysis in high-potassium erythrocytes (human and equine) and high-sodium (canine and bovine) ones has been studied. A decrease in hypertonic cryohemolysis level of human, canine and equine erythrocytes under long-term incubation at 37Â°C in contrast to bovine ones with typical reversible time dependence has been demonstrated almost in all media. Sensitivity of human erythrocytes to hypertonic cryohemolysis has been established to reduce in the series of Na+>K++Na+ >K+ >Li+ and in a reversible order for canine ones. Time dependencies of both equine and bovine erythrocyte hemolysis in media with different cation composition are practically similar. The results obtained are discussed from the point of view of peculiarities of erythrocyte ion transport systems of different mammalian species.